2019
DOI: 10.1155/2019/8510792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Person-Centredness in Rehabilitation for People Living with Dementia Is Needed: A Review of the Literature

Abstract: Background. With an expected increase in the prevalence of dementia, change in care policies and healthcare systems worldwide is needed. Rehabilitation is increasingly recognised as contributing to dementia care. Rehabilitation subscribes to person-centredness, and thus, evaluations of person-centredness in rehabilitation for people living with dementia are relevant in order for healthcare professionals to know how best to practice person-centredness. Aim. The aim of this study was to identify methods of evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…They perceived ICT integration as important in the early stroke screening, as many urgently need to be able to handle at least their mobile phone again in order to resume previous tasks, feel a sense of security and independence, and to compensate for remaining deficits. These results are in line with previous studies showing that stroke survivors, significant others and health professionals are interested in integrating ICT solutions in the rehabilitation process [4,16,23,28,29,47] because they can support stroke survivors' opportunities to engage in social activities [4,29,48], to give stroke survivors and significant others a greater feeling of independence [4,22,29], and, not least, to improve their quality of life [10,11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They perceived ICT integration as important in the early stroke screening, as many urgently need to be able to handle at least their mobile phone again in order to resume previous tasks, feel a sense of security and independence, and to compensate for remaining deficits. These results are in line with previous studies showing that stroke survivors, significant others and health professionals are interested in integrating ICT solutions in the rehabilitation process [4,16,23,28,29,47] because they can support stroke survivors' opportunities to engage in social activities [4,29,48], to give stroke survivors and significant others a greater feeling of independence [4,22,29], and, not least, to improve their quality of life [10,11].…”
Section: Discussionsupporting
confidence: 91%
“…individualized and tailored to respond to the individual's needs and with the recognition of significant others as crucial actors in the rehabilitation process [9,10]. A person-centred approach to the rehabilitation process has also been shown to promote both stroke survivors' and significant others' active involvement in their treatment and care, thus increasing their empowerment and autonomy [9][10][11][12] and reducing rehabilitation costs [7]. Furthermore, specialized rehabilitation programs including physiotherapy and occupational therapy have been shown to be effective in rehabilitation of declined functioning [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the total respondents, 57% (n = 90) reported that they were familiar with ICT, but only 31% (n = 49) used it therapeutically. Integrating ICT into the rehabilitation process can support clients' social participation [28,29] and contribute to improving their quality of life [30,31]. Healthcare professionals play a key role in providing appropriate ICT solutions to clients and caregivers [24,32].…”
Section: Familiarity With and Use Of Ictmentioning
confidence: 99%
“…Including studies which directly addressed person-centred rehabilitation in dementia might have produced a more comprehensive synthesis. However, a recent study by Christensen et al has shown that, so far, no studies have evaluated person-centredness in rehabilitation in dementia [39].…”
Section: Stage 4: Quality Assessment Of the Robustness Of The Synthesismentioning
confidence: 99%